A Comparative Study on Consumer Courts in Tamil Nadu & Kerala States - A Statistical Survey Report - Yamuna Krishna, B.; Suganya, Y. (Prabandhan: Indian Journal of Management, 2011)
Consumer Courts in India receive less attention from Central and State Governments, as it is a non-profit organization and a non-revenue department functioning for consumers benefit at National, State and District level. Supreme Court described the pathetic situation of Indian Consumers as "Society in which producers have secured the power to 'rob the rest' and public bodies are degenerating into storehouses of inaction, where papers do not move from one desk to another , leaving the common man helpless, bewildered and shocked. The society instead of bothering, complaining and fighting against it, is accepting it as part of life." This Research article compares the performance of Consumer Courts (State Commission and 30 District Forums) in Tamil Nadu with Consumer Courts (State Commission and 14 District Forums) in Kerala from November 2009 to September 2010. Statistical Reports published by National Commission at New Delhi since Inception on Number of cases Filed, Disposed, Pending, existing Vacancies and Non-Functioning courts was used for the comparison. Statistics reveal that Consumer courts in Kerala are functioning more effectively than Tamil Nadu. Apart from Statistics, there are other factors, which influence the effectiveness of consumer Courts such as Consumer's awareness level, their attitude and behavior, funds availability, support of State Government concerned, etc. Consumer Courts are like double edged swords with Government and consumers on either side. Neither the Government, nor the Consumers can be individually blamed for any cause and benefit.